Fish-specific TLR18 in Nile tilapia (Oreochromis niloticus) recruits MyD88 and TRIF to induce expression of effectors in NF-κB and IFN pathways in melanomacrophages. Issue 119 (December 2021) - Trung, Nguyen Bao; Nan, Fan-Hua; Lee, Meng-Chou; Loh, Jiun-Yan; Gong, Hong-Yi; Lu, Ming-Wei; Hang, Ho Thi; Lin, Yu-Lin; Lee, Po-Tsang
Abstract: Toll-like receptors (TLRs) are evolutionarily conserved proteins of pattern recognition receptors (PRRs) and play a crucial role in innate immune systems recognition of conserved pathogen-related molecular samples (PAMPs). We identified and characterized TLR18 from Nile tilapia ( Oreochromis niloticus ), OnTLR18, to elucidate its role in tissue expression patterns, modulation of gene expression after microbial challenge and TLR ligands, subcellular localization in fish and human cells, and the possible effectors TLR18 induces in a melanomacrophage-like cell line (tilapia head kidney (THK) cells). OnTLR18 expression was detected in all tissues examined, with the highest levels in the intestine and the lowest in the liver. OnTLR18 transcript was up-regulated in immune-related organs after bacterial and polyinosinic-polycytidylic acid (poly I:C) challenges and in the THK cells after lipopolysaccharide (LPS) stimulation. In transfected THK and human embryonic kidney (HEK) 293 cells, OnTLR18 localizes in the intracellular compartment. OnMyD88 and OnTRIF, but not OnTIRAP, were co-immunoprecipitated with OnTLR18, suggesting that the former two molecules are recruited by OnTLR18 as adaptors. The constitutively active form of OnTLR18 induced the production of pro-inflammatory cytokines, type I interferon (IFN), and antimicrobial peptides such as tumor necrosis factor α, interferon ( IFN ) d2.13, tilapia piscidin ( TP ) 2, TP3, TP4, and hepcidin in THK cells. Our results suggest that OnTLR18 plays an important role in innate immunity through initiating nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and IFN signaling pathways via OnMyD88 and OnTRIF and induces the production of various effectors in melanomacrophages. Highlights: OnTLR18 was cloned and characterized from Nile tilapia. The expression of OnTLR18 was induced after bacterial injection and LPS stimulation. OnTLR18 was localized to internal cellular compartments. OnTLR18 recruited MyD88 and TRIF as adaptors. Overexpression of truncated OnTLR18 promotes immune-related transcription factors.